Gender Differences Among Online Shopping Factors in Pakistan - Akhlaq, Ather; Ahmed, Ejaz (Organizations and Markets in Emerging Economies, 2016)
Pakistan is a huge consumer market, where very little is known about the aspects of consumers in online shopping environment. Consumer demographics such as gender are important factors in determining behaviour of individuals towards online shopping. This study finds relationships between gender and online shopping factors in Pakistan. With a survey sample of 286 respondents from various disciplines, exploratory factor analysis was used as an extraction method on the items of the proposed latent variables. MANOVA was then conducted to find gender differences among online shopping factors. Findings showed that shopping patterns differed between genders due to the influence of online shopping factors. This research may facilitate national and multinational organisations to streamline e-tailing strategies in order to gain business opportunities in emerging markets such as Pakistan.
Keywords: Pakistan; gender differences; online shopping; men; women; emerging markets